Revealing the functional importance of tyrosine and tryptophan of human hemoglobin for development of structural templates representing protein microenvironment - Chakraborty, Madhurima; Sen Banerjee, Nineesha; Ghosh, Deborin; Bhattacharya, Prabuddha; Ganguly, Tapan (Computational and Theoretical Chemistry, 2025)
Microenvironment surrounding Tyrosine (Tyr) / Tryptophan (Trp) and heme appear to characterize the UV-vis absorption spectra of human hemoglobin (HHb). Structural elucidation of HHb using multiple tools, that may contribute to its spectral properties, then indicate greater structural stability of subunit A and the significance of its heme, Tyr42 and Trp14. Mutagenesis of Tyr42 and Trp14 of subunit A to Glycine (Gly) further validate their contribution in determining the structural stability, physicochemical properties, functional properties, and secondary structure of HHb. Accordingly, the use of structural coordinates of Tyr42 and heme as the first cluster and Trp14, Tyr42 and heme as the second cluster to represent the microenvironment of HHb is assessed for the first time. The calculated (DFT) absorption and FTIR properties of both the clusters are in well agreement with experimental absorption and FTIR characteristics of whole HHb suggesting prospective biomedical applications of these clusters.
Keywords: Heme; Human hemoglobin; Nano-peptide cluster; Representative template; Trp14; Tyr42